Paracaesio brevidentata n. sp., a new snapper (Lutjanidae: Apsilinae) from Indonesia - White, William T.; Last, Peter R. (Zootaxa, 2012)
Paracaesio brevidentata, a new species of apsiline lutjanid fish from southeastern Indonesia, is described, bringing thetotal number of known species in this deepwater snapper genus to nine. The new species is distinguished from its conge-ners by the following combination of characters: very small teeth in jaws without enlarged canines, tubular lateral-linescales 71–73, pectoral-fin rays 18 or 19, caudal fin deeply forked, penultimate rays of soft dorsal and anal fins not longerthan adjacent rays, snout short, maxilla scaly and body purplish brown and caudal fin reddish with upper and lower lobessimilar in colour. Members of the genus are distinguished in a key. A specimen of Paracaesio caerulea from southeastern Indonesia represents the first record of this species from Indonesian waters.